531. Clinical Evaluation of the BioFire® FilmArray® Gastrointestinal (GI) Panel for use with Rectal Swab Specimens in Cary-Blair Media. (15th December 2022) - Goos, Jared; Neff, Crissy; Holmberg, Kristen; Lyons, Annie; Monroe, Nicole; Selvarangan, Rangaraj; Banerjee, Dithi; Hueschen, Leslie A; Chapin, Kimberle; Tansarli, Giannoula; Silbert, Suzane; Lima, Amorce; et al.
Abstract: Background: The BioFire® FilmArray® Gastrointestinal (GI) Panel provides results for 22 bacterial, viral, and protozoan pathogens responsible for GI infection in about an hour. This test is indicated for use with stool specimens in Cary-Blair media (SCB) as a specimen type. For many patients, a stool sample can be difficult to provide during a single clinic visit, potentially delaying diagnosis and treatment. Rectal swabs in Cary-Blair (RSCB; an off-label sample type) are a more convenient and faster specimen type to collect, as collection can occur during a patient's healthcare visit. The purpose of this study was to assess the performance of the GI Panel when testing RSCB compared to SCB. Methods: Paired SCB and RSCB specimens were collected from outpatient subjects with signs of GI infection and tested in parallel using the GI Panel. All detections were confirmed using culture (for some bacterial analytes) and PCR/sequencing. Performance of the GI Panel in RSCB versus SCB specimen types was assessed using the ratios (RSCB/SCB) of sensitivities and false positive rates (FPR). Positive percent agreement (PPA) and negative percent agreement (NPA) for the GI Panel test in RSCB compared to SCB were also evaluated. Results: A total of 299 paired SCB and RSCB specimens were collected and tested with the GI Panel. Detections for 17 of the 22 analytes on the GI Panel were observed in both specimen types. When comparing results from RSCB and SCB specimen types, the overall ratio of sensitivity was 0.86 and the overall ratio of FPR was 0.31. Further, overall PPA was 76.6% and overall NPA was 99.8%. Conclusion: Overall, the GI Panel is sensitive and specific for the rapid detection of many of the organisms responsible for GI infection when using either specimen type, however RSCB specimens have a lower diagnostic yield (i.e. fewer detections) compared to SCB. As a result, GI Panel performance for the RSCB is characterized as less sensitive compared to performance for SCB specimens. Acknowledging these limitations, the convenience and time-to-result benefits of the RSCB specimen type may aid in the effective diagnosis and management of GI infection in outpatient settings. The BioFire FilmArray GI Panel is not cleared or approved for use with rectal swabs in Cary-Blair . Disclosures: Jared Goos, PhD, bioMerieux: Employee|bioMerieux: Stocks/Bonds Crissy Neff, n/a, bioMerieux: Employee|bioMerieux: Stocks/Bonds Kristen Holmberg, n/a, bioMerieux: Employee Annie Lyons, n/a, bioMerieux: Employee Nicole Monroe, Dr. sc. nat., bioMerieux: Employee Rangaraj Selvarangan, BVSc, PhD, D(ABMM), FIDSA, F(AAM), BioFire: Grant/Research Support|Luminex: Grant/Research Support Kimberle Chapin, MD, Cepheid: Employee Bradley A. Connor, MD, BioMerieux: Advisor/Consultant Cynthia Andjelic, PhD, bioMerieux: Employee.